Robot clasificador por tamaño - Otero Cruz, Amaury Miguel (2010)
tool the robot arm Scorbot-ER 4u, which has been used to simulate one of the tasks that are very used in industry, in this case we made a classifier size, in which the robot arm collected the ball and tries to put in the correct place. And for its deployment we use several hardware resources such as robot arm Scorbot-ER 4u , the USB controller and the conveyor belt, and resources software as SCORBASE, which is used to maneuver the robot arm, we also use Robotcell , this program has the main objective to maneuver the robot arm in a virtual way to avoid fatal errors while using the SCORBASE. This thesis is divided basically into two chapters: